Influence Use of NGK Platinum C 7hvx Sparkplug toward Performance and Emision Gas of Four Stroke Motorcycle 110 Cc - Daud Pulo Mangesa (Jurnal Energi Dan Manufaktur, 2009)
Spark plug is a tool for producing an electric fire arc which has influences in process of combustion perfection, in internalcombustion engines. Spark plugs with electrode tip made of platinum, have good conducting character. The spark plugs areclaimed by their manufactures, are able to improve engines performance and able to reduce waste gases emission rate. Targets ofthis research is comparison C 7HSA Standard NGK Spark plug with NGK Platinum C 7HVX spark plug, in engine performance (power, efficiency, fuel consumptions ) and in waste gases emission rate ( CO rate level ) at engine rotation 2500 rpm, 3000 rpm,and 3500 rpm. 1 kg, 1,5 kg, 2 kg loads were used in waste gases emission rate examinations and fuel consumptions examinations.Data-processing methods were used in this research were descriptive analysis, correlation analysis and regression linieranalysis. Results of this research showed that by using NGK Platinum C 7HVX spark plug will be able to improve engineperformance ( power, efficiency, fuel consumptions ) and gases emission rate ( CO rate level ) if we compare with engine whichusing C 7HSA Standard NGK Spark plug.